Pengujian Aktivitas Antibakteri Gel Hand Sanitizer Kitosan Dengan Penambahan Ekstrak Daun Sirsak (Annona muricata L) - Mile, Lukman; Husain, Rahim; Stirman, Muh Rizki (Universitas Negeri Gorontalo, 2024)
The objective of this study was to analyze a chitosan hand sanitizer gel formulated with an 8 mL, 10 mL, 12 mL and 14 mL leaf extract (Annona muricata L) against the bacterial inhibition of Staphylococcus aureus and Eschericia coli. The research consists of several stages, namely the test of chemicals against bacterial barrier resistance of the test, the manufacture of leaf extract, the testing of characteristics of hand sanitizer gels with test parameters including homogenity, barrier and bacteria barrier. The research design uses a non-factorial complete randomized design (RAL) method. Data analysis using ANOVA, when there is influence then further testing Duncan. The results showed an average barrier inhibition of 10.17 mm for E. coli and 11.47 mm for S. aureus. The result of the extraction of 280 grams of sardine leaves yielded 238.08 grams extract, a randement of 117.6%, the handsanitzer has been mixed perfectly, the strength ranging from 5 to 7 cm. Hand sanitizer gel gives a real effect on the bacterial resistance of E. coli and S. aureus. The resulting inhibition for S.aureus bacteria is 7.3 mm to 17.5 mm and for E.coli bacteria is 7.2 mm to 9 mm. Base on these results, the average diameter of the inhibition formed is classified as moderate to strong.